Semi-automatic thresholding of RV trabeculation improves repeatability and diagnostic value in suspected pulmonary hypertension - Macdonald, Alistair; Salehi, Mahan; Alabed, Samer; Maiter, Ahmed; Goh, Ze Ming; Dwivedi, Krit; Johns, Chris; Cogliano, Marcella; Alandejani, Faisal; Condliffe, Robin; Wild, James M.; Kiely, David G.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Objectives: Right ventricle (RV) mass is an imaging biomarker of mean pulmonary artery pressure (MPAP) and pulmonary vascular resistance (PVR). Some methods of RV mass measurement on cardiac MRI (CMR) exclude RV trabeculation. This study assessed the reproducibility of measurement methods and evaluated whether the inclusion of trabeculation in RV mass affects diagnostic accuracy in suspected pulmonary hypertension (PH). Materials and Methods: Two populations were enrolled prospectively. (i) 144 patients with suspected PH who underwent CMR followed by right heart catheterisation (RHC). Total RV mass (including trabeculation) and compacted RV mass (excluding trabeculation) were measured on the end-diastolic CMR images using both semi-automated pixel-intensity-based thresholding and manual contouring techniques. (ii) 15 healthy volunteers and 15 patients with known PH. Interobserver agreement and scan-scan reproducibility were evaluated for RV mass measurements using the semi-automated thresholding and manual contouring techniques. Results: Total RV mass correlated more strongly with MPAP and PVR (r=0.59 and 0.63) than compacted RV mass (r=0.25 and 0.38). Using a diagnostic threshold of MPAP ≥25mmHg, ROC analysis showed better performance for total RV mass (AUC 0.77 and 0.81) compared to compacted RV mass (AUC 0.61 and 0.66) when both parameters were indexed for LV mass. Semi-automated thresholding was twice as fast as manual contouring (p<0.001). Conclusion: Using a semi-automated thresholding technique, inclusion of trabecular mass and indexing RV mass for LV mass (ventricular mass index), improves the diagnostic accuracy of CMR measurements in suspected PH.